Black Open Access in Ukraine: Analysis of Downloading Sci-Hub Publications by Ukrainian Internet Users - Nazarovets, S.A. (Science and Innovation, 2024)
Introduction. High subscription fees to scholarly research journals provoke researchers to use illegal channels of access to scientific information. Analysis of statistical data on downloads of scholarly research papers by Ukrainian Internet users from illegal web resource can help to define gaps in information provision at the institutional or the state level for each scientific field. Problem Statement. To conduct an analysis of behavior and geography of downloads of scholarly research publications from illegal web resource Sci-Hub by Ukrainian Internet users within the period from September 1, 2015 to February 29, 2016. Purpose. To assess the information needs of Ukrainian researchers who download scientific papers from Sci-Hub. Materials and Methods. The used file is available at public domain and contains complete data of downloads of scholarly research articles from Sci-Hub for the period from September 1, 2015 to February 29, 2016. Inquiries of users with Ukrainian IP-addresses have been selected. Using DOI of downloaded articles enables finding the publishers and journal brands with the help of CrossRef API, whereas using the All Science Journal Classification (ASJC) codes makes it possible to identify the subject. Results. The study has shown that the most documents downloaded related to natural sciences (primarily, chemistry, physics, and astronomy), with Elsevier publications being the most frequently inquired by Ukrainian users of Sci-Hub and Internet users from Kyiv downloading the papers most actively. Conclusion. The obtained data are important for understanding the information needs of Ukrainian researchers and can be used to formulate an optimal subscription policy for providing access to information resources at Ukrainian R&D institutions.